Environmental Transformation: A Systematic Literature Review on Green Innovation and Its Key Elements - Bakarim, Nur Aisya Addina Ahmad; Abdul Rahim, Ramita; Hamzah, Muhammad Iskandar (Advances in Social Sciences Research Journal, 2024)
Green Innovation is rapidly becoming a critical business component for many organizations. Thus, this study aims to examine Green Innovation practice research in the literature. At the same time, this study stresses that the practice of implementing Green Innovation may be used by any firm. A Systematic Literature Review (SLR) method is utilized for this aim, with 42 out of 125 studies meeting the search criteria. 24 of those studies are concerned with Green Innovation. Based on the findings of the investigations, five variables (green product innovation, green process innovation, green services innovation, green managerial innovation and green marketing innovation) have been highlighted as elements of Green Innovation for organizations. Therefore, this article will serve as a useful guide for firms looking to implement greener technologies through the usage of Green Innovation.